2011
DOI: 10.1103/physrevlett.106.247402
|View full text |Cite
|
Sign up to set email alerts
|

Dephasing of Triplet-Sideband Optical Emission of a Resonantly DrivenInAs/GaAsQuantum Dot inside a Microcavity

Abstract: Detailed properties of resonance fluorescence from a single quantum dot in a micropillar cavity are investigated, with particular focus on emission coherence in the dependence on optical driving field power and detuning. A power-dependent series over a wide range reveals characteristic Mollow triplet spectra with large Rabi splittings of |Ω|≤15  GHz. In particular, the effect of dephasing in terms of systematic spectral broadening ∝Ω(2) of the Mollow sidebands is observed as a strong fingerprint of excitation-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
172
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(189 citation statements)
references
References 27 publications
(34 reference statements)
16
172
1
Order By: Relevance
“…The full width at half maximum (FWHM) of the resonance is about 0.7 GHz. Although in four-wave mixing studies the zero-phonon linewidth has been shown to be limited by radiative decay to about 170 MHz 12,13 , PL linewidths and/or resonantly measured single QD excitation linewidths are usually found to lie in the range of 500 MHz to several GHz [5][6][7][8][9][10][11]17,[19][20][21] . The additional "apparent" broadening is due to spectral diffusion, a process by which the QD transition frequency is randomly shifted during the measurement 17 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The full width at half maximum (FWHM) of the resonance is about 0.7 GHz. Although in four-wave mixing studies the zero-phonon linewidth has been shown to be limited by radiative decay to about 170 MHz 12,13 , PL linewidths and/or resonantly measured single QD excitation linewidths are usually found to lie in the range of 500 MHz to several GHz [5][6][7][8][9][10][11]17,[19][20][21] . The additional "apparent" broadening is due to spectral diffusion, a process by which the QD transition frequency is randomly shifted during the measurement 17 .…”
mentioning
confidence: 99%
“…(2) with s/2π=0.7 GHz, chosen to coincide with the measured excitation linewidth of Fig. 1(c) which is also typical for InAs QDs [5][6][7][8][9][10][11]17,[19][20][21]23 . In comparison, Fig.…”
mentioning
confidence: 99%
“…The resonance spectrum consists of a single spectral line below saturation of a quantum emitter which develops into a triplet at powers above saturation of the emitter [1][2][3]. The spectral properties of the triplet strongly depends on pump power [4,5] and detuning of the excitation laser. The three closely spaced photon channels from the resonance fluorescence have different photon statistical signatures [6].…”
mentioning
confidence: 99%
“…In the case of strong light-matter coupling there is a strong interplay between exciton-phonon and light-matter interaction, which for example can be seen in the line-width broadening in the Mollow-Triplet [180,102]. The combined exciton-photon and exciton-phonon interaction in the strong coupling regime has been subject to many theoretical works [181,58,87,90,95,88,89,128,182,91].…”
Section: Rabi Rotationsmentioning
confidence: 99%
“…Also for dots in cavities phonons can play a decisive role, e.g., for the dephasing [87,88,89,90,91], the photon statistics [92,58,93,94], the indistinguishability of photons [95] as well as for providing a dot-cavity coupling in the case of non-resonant QD and cavity modes where phenomena like off-resonant cavity feeding have been found [96,82,97,98,99,100,101,102]. Although such systems are not at the focus of the present review, we note in passing that in this case, additional relaxation mechanisms, in particular cavity losses, may become of importance.…”
Section: Quantum Dot Modelmentioning
confidence: 99%